The Development of Nickel-Based Smelter in the Central Sulawesi Region Case Study in Morowali District - Jiang Liangliang; Ji Liang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Indonesia is a country that has large nickel reserves in the world. In addition to nickel being used for export, currently the government has made it mandatory to downstream nickel domestically. In addition, the potential for nickel in Indonesia also plays a role in increasing investment for state revenue, through smelter investments. Through the policy of banning the export of nickel ore, the continuity of the supply of crude nickel in the long term for the needs of domestic smelters is maintained.In the mineral mining industry, smelters are part of the production process, minerals mined from nature are usually still mixed with other materials, requiring further processing. The research method used is a qualitative research method with a descriptive approach. The case studies raised in this research are nickel mining companies in South Sulawesi, especially in Morowali Regency, which have integrated smelter processing facilities to produce matte nickel, which have many impacts on stakeholders, especially for the environment. The benefits generated by nickel processing smelter activities to stakeholders, namely the company, government, community and the surrounding environment.the future of the Indonesian nickel smelter industry depends on precise regulations and real implementation from the government to build a highly competitive domestic smelter industry so that independence in the national energy sector can be realized.